Dynamin‐related Irgm proteins modulate LPS‐induced caspase‐11 activation and septic shock. (30th October 2020) - Finethy, Ryan; Dockterman, Jacob; Kutsch, Miriam; Orench‐Rivera, Nichole; Wallace, Graham D; Piro, Anthony S; Luoma, Sarah; Haldar, Arun K; Hwang, Seungmin; Martinez, Jennifer; Kuehn, Meta J; Taylor, Gregory A; et al.
Abstract: Inflammation associated with gram‐negative bacterial infections is often instigated by the bacterial cell wall component lipopolysaccharide (LPS). LPS‐induced inflammation and resulting life‐threatening sepsis are mediated by the two distinct LPS receptors TLR4 and caspase‐11 (caspase‐4/‐5 in humans). Whereas the regulation of TLR4 activation by extracellular and phago‐endosomal LPS has been studied in great detail, auxiliary host factors that specifically modulate recognition of cytosolic LPS by caspase‐11 are largely unknown. This study identifies autophagy‐related and dynamin‐related membrane remodeling proteins belonging to the family of Immunity‐related GTPases M clade (IRGM) as negative regulators of caspase‐11 activation in macrophages. Phagocytes lacking expression of mouse isoform Irgm2 aberrantly activate caspase‐11‐dependent inflammatory responses when exposed to extracellular LPS, bacterial outer membrane vesicles, or gram‐negative bacteria. Consequently, Irgm2‐deficient mice display increased susceptibility to caspase‐11‐mediated septic shock in vivo . This Irgm2 phenotype is partly reversed by the simultaneous genetic deletion of the two additional Irgm paralogs Irgm1 and Irgm3, indicating that dysregulated Irgm isoform expression disrupts intracellular LPS processing pathways that limit LPS availability for caspase‐11 activation. Synopsis: Complex regulatory networks calibrate inflammation during an infection. Membrane‐remodeling IRGM proteins act as rheostats attenuating cytosolic sensing of bacterial LPS and protecting against LPS‐induced sepsis. Irgm2 depletion lowers the activation threshold of the cytosolic LPS sensor caspase‐11 in response to extracellular stimuli. Irgm2‐deficient animals succumb to endotoxemia due to increased caspase‐11‐mediated inflammation. Interregulatory relationships between Irgm paralogs determine host response to LPS. Abstract : Complex regulatory networks calibrate inflammation during an infection. Membrane‐remodeling IRGM proteins act as rheostats attenuating cytosolic sensing of bacterial LPS and protecting against LPS‐induced sepsis.